ИСПОЛЬЗОВАНИЕ РАСТЕНИЙ В СЕМЕЙНЫХ ОБРЯДАХ КАК ЭЛЕМЕНТ НАРОДНОЙ КУЛЬТУРЫ НА ПРИМЕРЕ НЕСКОЛЬКИХ СЕЛ ГАЙНОВСКОГО ПОВЕТА - Kuprianowicz, Adrian (Slavia Occidentalis, 2015)
The article presents, on the basis of elderberries, birch, St. John’s wort, yarrow, poppy, mint, wormwood, various rituals. The article also contains folk descriptions of plants, combined with the Polish literary language and Latin names. nettle using the aforementioned plants in magical practices, religious beliefs and superstitions connected with family traditions in Hajnówka District. A special attention is paid to the positive and negative influence of plants, for instance hanging elder over the door to ward off bad powers. It has been stated that members of old generations still use the majority of the described plants in various rituals. The article also contains folk descriptions of plants, combined with the Polish literary language and Latin names.